The Role of Naltrexone-Bupropion in Obesity Management: Current State of Knowledge - Grabowska, Martyna; Grabowska, Karolina; Kubicka, Jagoda; Wiśniewska, Aleksandra; Balik, Dominik; Kwaśniewska, Anna; Kaszyńska, Karolina; Dąbek, Jakub; Kosucka, Wiktoria; Lara, Joanna (Quality in Sport, 2025)
Introduction: Obesity is a chronic disease characterized by excessive fat accumulation, leading to significant health risks and numerous comorbidities. Its rising global prevalence demands effective management strategies1. The aim of the study: This article examines the role of combined naltrexone-bupropion therapy in obesity treatment. It focuses on its indications, mechanism of action, efficacy in weight management, safety profile, and potential side effects. Material and methods: A comprehensive literature review was performed using PubMed, Google Scholar, MedRxiv, and Scopus. The review included meta-analyses, randomized controlled trials, observational studies, and case reports assessing the pharmacotherapy of obesity with naltrexone-bupropion. Summary of current knowledge: Pharmacotherapy is recommended alongside lifestyle modifications for obesity management. Naltrexone-bupropion works by targeting both hypothalamic appetite control and the mesolimbic reward system, leading to significant weight loss in clinical studies. However, its use is often accompanied by mild to moderate adverse effects, such as nausea and headaches. Conclusions: Obesity requires a multifaceted treatment approach. Naltrexone-bupropion offers a promising adjunct to diet and exercise but long-term safety and individualized treatment strategies need further investigation.